2003
DOI: 10.1002/art.11023
|View full text |Cite
|
Sign up to set email alerts
|

Effects of antiinflammatory drugs on arthritic cartilage: A high‐frequency quantitative ultrasound study in rats

Abstract: Objective. To evaluate the ability of 55-MHz quantitative ultrasound (US) to detect the in vivo effects of experimental arthritis, as well as those of two antiinflammatory drugs, naproxen (NPX) and dexamethasone (DEX), on cartilage and subchondral bone.Methods. Arthritis was induced in both knees of 108 rats by intraarticular injection of zymosan (ZYM). Two groups of arthritic rats (n ‫؍‬ 36 per group) were treated daily with either NPX (10 mg/kg/day) or DEX (0.1 mg/kg/day). Using a 3-dimensional US microscope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…Cherin et al (20) demonstrated a relationship between quantitative ultrasound and maturation-related changes in rat cartilage, while Jaffre et al (21) reported that quantitative 55-MHz ultrasound allowed detection of early cartilage lesions due to experimental arthritis, as well as enabling monitoring of the effects of antiinflammatory drugs. Therefore, high-frequency ultrasonography could be useful for investigating structural changes in the cartilage matrix and evaluating the efficacy of specific therapeutic agents.…”
Section: Discussionmentioning
confidence: 99%
“…Cherin et al (20) demonstrated a relationship between quantitative ultrasound and maturation-related changes in rat cartilage, while Jaffre et al (21) reported that quantitative 55-MHz ultrasound allowed detection of early cartilage lesions due to experimental arthritis, as well as enabling monitoring of the effects of antiinflammatory drugs. Therefore, high-frequency ultrasonography could be useful for investigating structural changes in the cartilage matrix and evaluating the efficacy of specific therapeutic agents.…”
Section: Discussionmentioning
confidence: 99%
“…Results of these studies are variable. For example, treatment with aspirin, diclofenac, ibuprofen, indomethacin, and tenoxicam, was associated with impaired bone healing in rats and rabbits [69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87]. The main effects observed in those models included inhibition of Haversian (cortical bone) remodeling, alterations in spinal fusions, poor mineralization of bone matrix, decreased osteoid formation and callus bone formation, decreased bone mineral content, reduced mechanical strength of replacement tissue, decreased amounts of cortical bone and inhibition of new bone formation [73,77,[80][81][82][88][89][90][91][92].…”
Section: Effects Of Non-selective Nsaids On Bone Healingmentioning
confidence: 99%
“…All previous studies using the same model have described findings more than 10 days after induction. mortem analysis, examined the disease at more advanced stages, restricted imaging to a single modality (either MRI or CT), with or without direct histological correlation (1,7,(12)(13)(14). In our study, high-resolution microMRI and microCT successfully detected very early inflammatory changes within the first week of injection of the adjuvant.…”
Section: Discussionmentioning
confidence: 87%